2023
DOI: 10.1139/tcsme-2022-0143
|View full text |Cite
|
Sign up to set email alerts
|

A doubt–confirmation-based visual detection method for foreign object debris aided by assembly models

Abstract: Foreign object debris (FOD) impacts significantly on the quality control during product assembly because it usually causes product failure. The vision-based method as a nondestructive and efficient technology has become an important approach to FOD detection. However, it faces two important challenges: (1) inexhaustible types (almost any object can become FOD) and (2) unpredictable locations (FOD can appear almost anywhere on surface of a product). Therefore, this paper proposes an FOD visual detection method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…There is limited research on this topic, mainly due to the challenges in vision-based locating of foreign object debris in a complex assembled product, and its recognition falls under the category of open-set problems [3]. Nevertheless, this task can be transformed into a joint task of empirical sampling and pattern comparison within this framework.…”
Section: Foreign Object Debrismentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited research on this topic, mainly due to the challenges in vision-based locating of foreign object debris in a complex assembled product, and its recognition falls under the category of open-set problems [3]. Nevertheless, this task can be transformed into a joint task of empirical sampling and pattern comparison within this framework.…”
Section: Foreign Object Debrismentioning
confidence: 99%
“…If so, further identification of the type of anomaly is also needed. This demand for flexible capture makes many traditional industrial vision solutions [3][4][5] (as shown in Figure 1a-d) no longer applicable, and the demand for intelligent judgement makes some portable solutions (as shown in Figure 1e) only available for auxiliary visualization and active projection [6,7], while the analysis still relies on humans; Figure 1. The challenges that current vision-based inspection will face in future manufacturing models are already emerging in the appearance quality assurance of the complex product assembly in high-end equipment manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%